PELAKSANAAN DIVERSI TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DI BAWAH UMUR DI POLRES KUTAI TIMUR - Supriadi Supriadi (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Children are a mandate from God Almighty, which is inherently inherent in dignity and worthy of being upheld as whole human beings because children are the next generation of the nation and have a very important role to lead and advance the nation. The important role carried by children is what makes parents, the community and even the government must guarantee the lives of children. In this case the state has an obligation to guarantee the rights of every child to their survival, growth and development as well as the right to protection from violence and discrimination. Children as criminals must take responsibility for their actions. This must be done so as to provide lessons to children, so that in the future the child does not repeat the same mistakes. Punishing children must pay attention to aspects of child development and the best interests of the child. Children who have committed crimes must remain protected and pay attention to their rights so as not to interfere or even damage the child's growing up period. This is what underlies the formation of the juvenile justice system. Diversity in essence also has the goal of avoiding children and the negative impact of criminal application. Diversion also has the essence of ensuring that children grow and develop both physically and mentally. Judging theoretically from the concept of the objective of punishment, the transfer of the process and the judicial process to the non-judicial process of children who commit narcotics abuse will be seen as relevant. Based on the reasons for selecting the titles described above, the problems in this thesis are as follows: (1) What is the legal position of diversion for underage narcotics offenders in East Kutai Regional Police? (2) What are the obstacles faced by the police in implementing diversification of minors as narcotics offenders? Then it can be concluded (1) The legal position of diversion against children of narcotics abusers in the perspective of the development of criminal law is a non-penal policy measure for handling children who commit child crime, because its handling is diverted from the path of the juvenile justice system. Diversi departs from the assumption that the process of handling minors through the juvenile justice system is more likely to be negative than positive for children's development. With regard to handling children as narcotics abusers, the main problems arising from the juvenile criminal justice process or a criminal verdict are the Stigma attached to convicted of narcotics abuse after the completion of the criminal justice process. The tendency of increasing child abuse of narcotics, encourages efforts to deal with and deal specifically with it in the field of child criminal law. The concept of diversion that is regulated in the Criminal Justice System in Indonesia is to place an obligation to diversify in each stage of the judicial process (investigation, prosecution and trial). (2) Lack of coordination between agencies implementing the diversion that one of the obstacles to the implementation of the diversion in the East Kutai Police Station is the lack of Community Guidance personnel, namely only a few PK personnel handling client children with Bapas working area coverage reaching 18 districts, as well as the time of child detention. short. and Lack of public confidence in the rules of implementing diversion. Even though it has been regulated in the law, the idea of diversion is still hindered by the views of the people who tend to distrust and without thinking about the impact that will be faced by the child. Diversion is a very important policy applied to protect children from the formal justice process. However, sometimes the authorities still hesitate to run it. This is because the demands of the community, politics, or others are considered by the authorities. Officials are also afraid of being blamed if the child repeats his actions later. The public is also still pessimistic about the diversion policy of the authorities which will harm the interests of certain parties. Keywords: Diversity, Children of Criminal Acts, Narcotics